2014
DOI: 10.1177/0267323114544864
|View full text |Cite
|
Sign up to set email alerts
|

Slovak political debates: Functional theory in a multi-party system

Abstract: This article examines a content analysis of the televised political debates prior to the 2012 elections in Slovakia. The analysis is based on the functional theory of campaign discourse by William L. Benoit. The goal of the work is to test the theory and its applicability in contexts other than the political system of the United States. In order to achieve this goal, we also make use of the findings of previous studies from the non-American environment. We have found that if Benoit’s methods were strictly obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 7 publications
0
12
0
1
Order By: Relevance
“…In recent years, however, the functional theory of political campaign discourse has been applied to several elections in various countries outside of the US. So far, functional theory has been used to analyse political campaign discourse in Slovakia (Hrbková & Zagrapan, 2014), the United Kingdom (Benoit & Benoit-Bryan, 2013), France (Choi & Benoit, 2013), Spain (Herrero & Benoit, 2009), Israel (Benoit & Sheafer, 2006), Taiwan (Benoit, Wen, & Yu, 2007), Romania (Cmeciu & Patrut, 2010), Ukraine (Benoit & Klyukovski, 2006), Germany (Benoit & Hemmer, 2007), Korea (Lee & Benoit, 2004, 2005, Finland (Isotalus 2010(Isotalus , 2011, Canada (Benoit, 2011;Benoit & Henson, 2007), and Australia (Benoit & Henson, 2007). Applying functional theory to research the political campaign discourse in countries other than the US has raised the question of whether the theory is too culturally limited to be useful in political systems different from that of the US.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, however, the functional theory of political campaign discourse has been applied to several elections in various countries outside of the US. So far, functional theory has been used to analyse political campaign discourse in Slovakia (Hrbková & Zagrapan, 2014), the United Kingdom (Benoit & Benoit-Bryan, 2013), France (Choi & Benoit, 2013), Spain (Herrero & Benoit, 2009), Israel (Benoit & Sheafer, 2006), Taiwan (Benoit, Wen, & Yu, 2007), Romania (Cmeciu & Patrut, 2010), Ukraine (Benoit & Klyukovski, 2006), Germany (Benoit & Hemmer, 2007), Korea (Lee & Benoit, 2004, 2005, Finland (Isotalus 2010(Isotalus , 2011, Canada (Benoit, 2011;Benoit & Henson, 2007), and Australia (Benoit & Henson, 2007). Applying functional theory to research the political campaign discourse in countries other than the US has raised the question of whether the theory is too culturally limited to be useful in political systems different from that of the US.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cmeciu and Patrut (2010) agreed with this critique, arguing that political campaign discourse is not consistent across borders and cultures; indeed, their study of the 2009 Romanian presidential debates revealed the debates were not focused on acclaims and policy, as argued by the functional theory, but instead on attacks and defences. Also Hrbková and Zagrapan's (2014) research of the 2012 election debates in Slovakia reached similar conclusions, arguing the categories of content analysis should be expanded as with the current categories more than 30 percent of the content of the debates would be excluded from the analysis -an argument also made by Isotalus (2011). Nevertheless, from the content analysed, acclaims were still the most common category, followed by attacks, which means the results reached in Slovakia are at least somewhat similar to those reached in the United States.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Lock and Harris (1996: 21) explain that political marketing "is concerned with communicating with party members, media and prospective sources of funding as well as the electorate", making political communication a central function in political marketing (Newman, 1999). Political communication has generated significant research interest in recent years (see for example Hrbková & Zagrapan, 2014;Miller & McKerrow, 2010;Petithomme, 2010 andStromback &Van Aelst, 2013), involving a range of communication tools used to convey a clear message to the electorate in order to win elections. Various facets of political communication have accordingly been investigated, including the importance of message differentiation (Kitschelt, 1994;Lees-Marshment, et al 2014;Spoon, 2009).…”
Section: Political Communicationmentioning
confidence: 99%
“…For example, several studies (Benoit & Airne, 2005;Benoit & Harthcock, 1999) have highlighted the use of acclaims more frequently than attacks whilst attacks are used more frequently than defences, particularly by political challenges (Airne & Benoit, 2005;Benoit, 2007;Lau & Pomper, 2004). Furthermore, defensive tactics possess a number of potential disadvantages: 1) defending against attacks will frequently take a candidate 'off-message' (Hrbková & Zagrapan, 2014); 2) defences may be perceived as reactive rather than proactive which may be construed by the electorate as a negative quality (Gruber & Bale, 2014) and 3) defending against an attack invariably involves identifying or notifying voters of a latent weakness (Benoit et al 2010).…”
Section: Candidates Generate Voter Preferences Via Acclaiming (Commenmentioning
confidence: 99%